CICERO'S USE OF AESCHYLUS' ORESTEIA IN THE PRO MILONE. (6th May 2016) - Brook, Adriana
Abstract : Early in the Pro Milone, Cicero's defence of Titus Annius Milo on trial for the murder of Publius Clodius Pulcher, the orator presents a list of exemplary figures from Roman history whose deeds offer parallels for Milo's alleged crime. Though these men murdered political enemies, they were nonetheless considered justified in their actions by their Roman peers. In emphatic and memorable last place in this list is an example drawn not from Roman history but from Greek tragedy: